2014
DOI: 10.1073/pnas.1409171111
|View full text |Cite
|
Sign up to set email alerts
|

Potential antigenic explanation for atypical H1N1 infections among middle-aged adults during the 2013–2014 influenza season

Abstract: Influenza viruses typically cause the most severe disease in children and elderly individuals. However, H1N1 viruses disproportionately affected middle-aged adults during the 2013-2014 influenza season. Although H1N1 viruses recently acquired several mutations in the hemagglutinin (HA) glycoprotein, classic serological tests used by surveillance laboratories indicate that these mutations do not change antigenic properties of the virus. Here, we show that one of these mutations is located in a region of HA targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
257
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(282 citation statements)
references
References 30 publications
22
257
3
Order By: Relevance
“…Of the 41 sera samples screened after vaccination (MN titer >1:40), we found a second example in which the sera lost the ability to neutralize H1N1 viruses with K163 substitutions (Figure 6). These findings with sera are consistent with those of the survey of Linderman et al (14), who found up to 42% of sera from donors born before 1979 showed reduced reactivity with clade 6B H1N1pdm09 isolates. Both our sera were from donors born before 1982 (2 of 28).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Of the 41 sera samples screened after vaccination (MN titer >1:40), we found a second example in which the sera lost the ability to neutralize H1N1 viruses with K163 substitutions (Figure 6). These findings with sera are consistent with those of the survey of Linderman et al (14), who found up to 42% of sera from donors born before 1979 showed reduced reactivity with clade 6B H1N1pdm09 isolates. Both our sera were from donors born before 1982 (2 of 28).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our detailed clonal analysis extend two recent serological studies of the human antibody response to the H1N1pdm09 virus (14,37). Li et al have shown that human individuals born between 1983 and 1996 (after donor H), who were exposed in early life to former seasonal H1 viruses that retained K130, narrowly focused their antibody response on this region on exposure to H1N1pdm09 (37).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations